Egg quality traits of indigenous, exotic and crossbred chickens (Gallus domesticus L.) in Rajshahi, Bangladesh - Islam, M Saiful; Dutta, Ripon Kumar (Journal of Life and Earth Science, 2011)
This study was aimed at investigating the external and internal egg quality traits along with their correlation values of an indigenous (Deshi), three exotics (Cobb 500 of Broiler, Fayoumi, and RIR) and a crossbred (Sonali derived from RIR?× Fayoumi?) chicken breeds available in Rajshahi. From a total of 50 eggs (5 breeds × 10 replicates each), the external quality traits such as gross egg weight (EW), egg length (L), egg width (W), egg volume (EV), shell weight (SW), shell ratio (SR) and egg shape index (ESI), and the internal quality traits like yolk weight (YW), albumen weight (AW), yolk ratio (YR) and albumin ratio (AR) were determined. Results showed that highly significant differences exist for both external and internal egg quality traits between the genetic groups of chicken (P<0.001). Even though RIR showed the highest EW and EV and Fayoumi had the lowest for both traits, AR was in the sequence of Cobb 500 > RIR> Indigenous> Fayoumi> Sonali. Phenotypic correlations among the egg quality traits revealed that EV was not significantly correlated with EW except for Sonali (P<0.001). The association between EW and ESI was negative in all the chickens except Sonali. However, EW was significantly correlated with the AW in RIR (P<0.001), Cobb 500 (P<0.01) and Sonali (P<0.01). Moreover, the EW was significantly correlated with YW only in Fayoumi and RIR (P<0.05). In view of the cholesterol, fat and antioxidant contents of the hen’s egg, a higher AR is healthier than a higher YR. The present findings therefore suggest that Cobb 500, RIR and Indigenous eggs are healthier than Fayoumi and Sonali eggs that contain higher YR. Key words: Egg quality traits; phenotypic correlation; Indigenous; exotic and crossbred chickens DOI: 10.3329/jles.v5i0.7352 J. Life Earth Sci., Vol. 5: 63-67, 2010